On-water and dryland vertical jump in water polo players - Platanou, T. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The performance of the vertical jump constitutes a fundamental technical ability in many team sports, including water polo. The purpose of the present study was therefore twofold: firstly, to evaluate the ability of water polo players to move their bodies vertically off the water (on-water vertical jump), and secondly, to determine on the same players their lower bodies¹ explosive power ability, while performing a vertical jump on dry-land (dry-land vertical jump). We also investigated whether the performance of the on-water vertical jump depends on the position of the players in the game and on competition. Methods: Forty-three water polo players, were tested on-water and on dry-land. The on-water vertical jump was assessed using a board with a centimeter scale attached on it. A video camera that was placed facing the board was used to record the trials of the players. Results: The mean value of the on-water vertical jump was 68.3±4.6 cm, whereas the mean value of the dry-land vertical jump was 49.6±6.5 cm. The coefficient between the 2 jumps was very low (r=0.25). Significant differences between the 2 jumps according to the players¹ positions and to their level of competitiveness were found. Conclusion: The performance of the on-water vertical jump correlates poorly with the explosive ability of the lower body as that which was assessed by the dry-land vertical jump. Furthermore, the ability to move the body vertically on-water differs significantly among players, depending on their position and on the level of competitiveness.